An Hg2+-selective chemosensor based on the self-assembly of a novel amphiphilic block copolymer bearing rhodamine 6G derivative moieties in purely aqueous media1. Issue 6 (21st March 2015) - Wang, Zhao; Yang, Zhongkui; Gao, Tao; He, Jingwen; Gong, Laijiang; Lu, Yanbing; Xiong, Yuanqin; Xu, Weijian
<x xml:space="preserve">Abstract</x> An amphiphilic block copolymer-based colorimetric and fluorescent chemosensor for Hg2+ was prepared, which was synthesized by sequential RAFT polymerization of NIPAM and R6GDM (a novel Hg2+-sensitive rhodamine monomer).